Hospital visitors as controls in case-control studies - Mendonça Gulnar Azevedo S; Eluf-Neto José (Universidade de São Paulo, 2001)
OBJECTIVE: Selecting controls is one of the most difficult tasks in the design of case-control studies. Hospital controls may be inadequate and random controls drawn from the base population may be unavailable. The aim was to assess the use of hospital visitors as controls in a case-control study on the association of organochlorinated compounds and other risk factors for breast cancer conducted in the main hospital of the "Instituto Nacional de Câncer" -- INCA (National Cancer Institute) in Rio de Janeiro (Brazil). METHODS: The study included 177 incident cases and 377 controls recruited among female visitors. Three different models of control group composition were compared: Model 1, with all selected visitors; Model 2, excluding women visiting relatives with breast cancer; and Model 3, excluding all women visiting relatives with any type of cancer. Odds ratios (OR) and 95% confidence intervals were calculated to test the associations. RESULTS: Age-adjusted OR for breast cancer associated with risk factors other than family history of cancer, except smoking and breast size, were similar in the three models. Regarding family history of all cancers, except for breast cancer, there was a decreased risk in Models 1 and 2, while in Model 3 there was an increased risk, but not statistically significant. Family history of breast cancer was a risk factor in Models 2 and 3, but no association was found in Model 1. In multivariate analysis a significant risk of breast cancer was found when there was a family history of breast cancer in Models 2 and 3 but not in Model 1. CONCLUSIONS: These results indicate that while investigating risk factors unrelated to family history of cancer, the use of hospital visitors as controls may be a valid and feasible alternative.